2020
DOI: 10.5032/jae.2020.01152
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Virtual Reality Technology on Welding Skill Performance

Trent Wells,
Greg Miller

Abstract: Simulator technologies such as virtual reality (VR) can serve as practical tools in the educational process. VR technology applications can be effectively used for weld process training. Weld process training can often be found in university-level agricultural education settings. We sought to determine if using a VR technology application within the context of a one-hour-long gas metal arc welding (GMAW) process training impacted welding skill performance as determined by certified welding inspectors (CWIs) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…More recent research attention has focused on MR-enhanced tele-welding paradigms [22]. It was verified in [23] that there were no statistically significant differences in the total welding scores between participants in the physical welding group and the mixed realitybased welding groups. The mixed reality welding user interface gives operators the ability to perform welding at a distance while maintaining a level of manipulation [24].…”
Section: Related Workmentioning
confidence: 95%
“…More recent research attention has focused on MR-enhanced tele-welding paradigms [22]. It was verified in [23] that there were no statistically significant differences in the total welding scores between participants in the physical welding group and the mixed realitybased welding groups. The mixed reality welding user interface gives operators the ability to perform welding at a distance while maintaining a level of manipulation [24].…”
Section: Related Workmentioning
confidence: 95%
“…For students who fail meet the inspection standards, this course planned welding remedial teaching, which is equipped with VR welding equipment to provide exercises and tests to help students improve their welding skills. With the application of VR welding equipment, students can practice continuously by applying the trial and error method, which helps students to solve problems and receive remedial learning [17].…”
Section: Provide Practice and Guidance For Diversified Virtual And Re...mentioning
confidence: 99%
“…Going back to the roots, the fundamental solution lies in the reform and practice of welding worker training and education. According to a review of the traditional welding technical personnel training models, which feature high monetary costs, long cycle equipment, high manpower requirements, extensive raw materials, and high energy costs [17], such courses consume a large amount of welding rods and workpiece materials and produce toxic and harmful gases, dust, ultraviolet rays, radiation, and electromagnetic pollution to cause certain harm to the students' health [18]. Therefore, actively considering and improving technical and vocational education is a worthy topic in order to teach engineering educational units how to apply emerging technologies to welding personnel training, improve the learning effectiveness of the students' welding knowledge, reduce the input cost of welding training, reduce the physical hazards caused by the welding training process, and provide real practice and safe experience [19].…”
Section: Introductionmentioning
confidence: 99%
“…Much progress has been made regarding the advancements of VR technology (Bailenson, 2018;Brooks, 1999), especially considering the diversity of fields VR technology has been applied in. Throughout the past three decades, VR technology has been studied in the contexts of: (1) weld process training (Byrd, 2014;Byrd et al, 2015;Stone et al, 2011;Stone et al, 2013;Wells & Miller, 2020), (2) medical science (Cope & Fenton-Lee, 2008;Gallagher et al, 2003;Gor et al, 2003;Kilmon et al, 2010;Seymour et al, 2002), (3) safety training (Filigenzi et al, 2000), (4) science education (Nadolny et al, 2013), and (5) first responder training (Bliss et al, 1997). VR technology has great potential to positively impact the educational experience (Bailenson, 2018), particularly in laboratory-based settings (Potkonjak et al, 2016) such as a university-level agricultural mechanics course.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps using a VR technology application could be a practical approach to teaching and learning in a university-level course focused on skill development. Considering that prior research conducted by Byrd (2014), Stone et al (2011), andWells andMiller (2020) has indicated VR technology can help to effectively develop welding-related psychomotor skills, how would students perceive using such tools in a university-level course setting? Spicer and Stratford (2001) noted students in universitylevel settings often find value in using VR technology to help supplement the learning experiences offered in their courses.…”
Section: Introductionmentioning
confidence: 99%